The Role Of Research And Development In Supporting Innovation In Entrepreneurial Institutions - Ghozal ,Nabila; Harnane, Nadjoua (جامعة الوادي University of Eloued, 2024)
This research paper, we aimed to address the topic of innovation in entrepreneurial organizations through research and study, and the research and development strategy adopted by entrepreneurial organizations to support and develop these organizations, and to identify the extent of the impact of research and development on supporting innovation in assista-soins as a leading model for emerging organizations in Algeria, where the issue of the study centered on how research and development can contribute to supporting innovation in entrepreneurial organizations. The study concluded that R&D plays a pivotal role in supporting and promoting innovation in entrepreneurial organizations, which gives them excellence and continuity in internal markets and even expansion outside the country, as Assistasoins came to the forefront like other companies that have achieved great success in the local market, mainly due to the entrepreneurial spirit of its founders and their competence and scientific qualifications.
مقال
Keywords: innovation; start-up; Assista-soins